Caso dermatológico: Talon noir de localização atípica - Carvalho, S. (2014)
The talon noir is a post-traumatic purpuric dermatosis of acral localization, histologically characterized by the presence of blood within the stratum corneum. It is often observed in young athletes as macules of black-brown coloration on both heels. In cases of diagnostic uncertainty, curettage and dermoscopy are useful tools. No treatment is necessary because the lesions tend to resolve spontaneously. We describe the case of a five-year--old boy with an atypical talon noir